Correlation Of Maternal Characteristics (Age, Parity, BMI) With Success Of Labor Induction Oxytocin Drip - Siti Asiyah; Widi Astuti, Wuri; silviya, Linda (Chakra Brahmanda Lentera Institute, 2024)
Background: : Labor induction with oxytocin drip is an alternative action that can be used to overcome complications in the labor process. The study aims to determine the correlation between maternal characteristics (age, parity, BMI) and the success of labor induction oxytocin drips in Aminah Hospital Blitar City. Methods: The research design was cohort retrospective—Independent data on maternal age, parity, and BMI. Dependent data is the success of oxytocin drip labor induction. Data was obtained through medical record status with 50 respondent samples. It was taken using proportional random sampling, Inclusion criteria for oxytocin drip labor induction starting in the latent phase, and collected using the data collection instrument sheet on July 12 - 30, 2023. The data analysis used the Chi-Square test. Results: Results of the study showed that there was a relationship between maternal age and labor induction success with oxytocin drip, with an Asymp Sig (0,000) < α (0,05). There was no relationship between parity and labor induction success with oxytocin drip, with an Asymp Sig (0,157) > α (0,05). There was a relationship between BMI and labor induction success with oxytocin drip, with an Asymp Sig (0,000) < α (0,05). Conclusion: Maternal age and BMI affect the success of labor induction, so women should give birth in a safe age range, which is 20-35 years, and a BMI of 18,5-24,9 kg/m2 will reduce the risk of failure in the labor process, especially labor with oxytocin drip induction.